Physicochemical and biological parameters of vitivinicultural residues and their potential effect on soil helminths - Sosa-Vilca, René Germán (2025)
Vitivinicultural residues constitute a lignocellulosic biomass that, when transformed by yeasts and enzymes, can modify soil conditions and influence the ecology of soil helminths. The objective of this study was to evaluate the physicochemical and biological parameters of vitivinicultural residues and describe their potential effects on soil helminths. The research was descriptive, observational, and exploratory, conducted between March and June 2025 in the laboratories of the Professional School of Agroindustrial Engineering at the Universidad Nacional de Moquegua, Peru. Twenty-four samples of grape pomace (Vitis vinifera L.) were analyzed after treatments involving alkaline hydrolysis, enzymatic hydrolysis, and yeast fermentation. The results showed that enzymatic hydrolysis yielded the highest pH (6.0), temperature (60 °C), reducing sugars (34.6 g/L), and ethanol (25%), generating less acidic conditions, greater energy availability, and organic enrichment. These changes may favor the survival of free-living nematodes, select for more resistant species, and increase the population density of soil helminths. It is concluded that the synergistic action of yeasts and enzymes transforms vitivinicultural residues into a key ecological factor in the helminthological dynamics of agricultural soils.